Histopathological Findings of Pancreaticoduodenectomy Specimens in a Tertiary Care Hospital in Nepal - Karki, Shovana; Shrestha, Sonafi; Tiwari, Sansar B; Lakhey, Paleswan Joshi (Journal of Institute of Medicine Nepal, 2021)
Introduction: Among the gastrointestinal malignancies, 5% of the tumors comprise peri-ampullary carcinomas. Adenocarcinoma is the commonest malignancy in the peri-ampullary region. The important histopathological prognostic factors are tumor size, location, extension, resected marginal status, lymphovascular (LVI) and perineural invasion (PNI) and lymph nodal status. This study was conducted to analyze the lesions and to describe the associated histopathological parameters. Methods: This study was carried out in the Department of Pathology, TUTH, Kathmandu, includes pancreatico-duodenectomy specimens submitted from April 2016 to September 2020. The related details were obtained from the archives of reports in the Department. Statistical analysis was performed using IBM SPSS v26. Results: Among 111 specimens, 100 (90%) malignant lesions, 10 (9.1%) benign lesions and 1(0.9%) pre-malignant lesions were seen. M:F ratio was 1.2:1 with mean age 55.5 years. Ampulla was the most common site of malignancy (61%) and adenocarcinoma was the commonest histological type. Chronic pancreatitis (4.5%) accounted for most of the benign lesions. Ampullary and pancreatic malignancies were detected in T2 stage, 55.7% and 77.8% respectively. LVI was seen in 61% and PNI in 72% of pancreatic malignancies. Positive resected margin was seen in 6% of malignancies. SMA was the most common positive margin. Conclusion: Pancreatico-duodenectomy was performed mostly for adenocarcinomas of ampulla. Pancreatic tumors were common in the older age group and they presented with LVI and PNI and at a higher T and N status as compared to ampullary or duodenal tumors.